The Influence of Example Non-Example Learning Model on Pancasila Education Learning Outcomes of Class V Students of UPTD SD Negeri 122384 Pematangsiantar - Pasaribu, Yulika; Panggabean, Eva Saryati; Tobing, Minar Trisnawati Lumban (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to determine: The Effect of Example Non-Example Learning Model on Pancasila Education Learning Outcomes of Class V Students of UPTD SD Negeri 122384 Pematangsiantar The type of research used in this study is Quantitative Research. The research design that will be used is experimental, with the form of Pre-Experimental Design with "one group pretest posttest design". The sample in this study were 20 class V students of UPTD SD Negeri 122384 Pematangsiantar, where 8 were male and 12 were female. The instrument used in this study was in the form of multiple-choice questions. Hypothesis testing shows that there is a significant influence on this study from the data that has been tested, the data can be seen from the data analysis obtained the average results of the pretest (47.25) and posttest (84.75). Based on the results of the study, it can be concluded that there is an influence of the Example Non-Example Learning Model on the Learning Outcomes of Pancasila Education for Class V Students of UPTD SD Negeri 122384 Pematangsiantar, this is proven by the results of the hypothesis test showing that t count is more than t table (9.59 more than 1.729) this fact shows that the t count obtained is very significant. Thus, it is concluded that there is an influence of the Example Non-Example learning model on the learning outcomes of Pancasila Education for class V students of UPTD SD Negeri 122384 Pematangsiantar.